2018
DOI: 10.1111/odi.12965
|View full text |Cite
|
Sign up to set email alerts
|

Association of long interspersed nucleotide element‐1 and interferon regulatory factor 6 methylation changes with nonsyndromic cleft lip with or without cleft palate

Abstract: Our study suggested that aberrant methylation of LINE-1 and IRF6 might contribute to the development of NSCL/Ps. Further studies are needed to replicate the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Long interspersed nucleotide element‐1 (LINE‐1) is a marker of global DNA methylation. Studies have reported differential global DNA methylation patterns between NSOFC and controls using the methylation levels of LINE‐1 (Cáceres‐Rojas et al, 2020; Khan et al, 2018, 2019; Li et al, 2019). There is evidence to suggest that genetic variations (c.C677T and c.A1298C) in the MTHFR gene lead to low DNA methylation levels (Frosst et al, 1995; van der Put et al, 1998).…”
Section: Epigeneticsmentioning
confidence: 99%
“…Long interspersed nucleotide element‐1 (LINE‐1) is a marker of global DNA methylation. Studies have reported differential global DNA methylation patterns between NSOFC and controls using the methylation levels of LINE‐1 (Cáceres‐Rojas et al, 2020; Khan et al, 2018, 2019; Li et al, 2019). There is evidence to suggest that genetic variations (c.C677T and c.A1298C) in the MTHFR gene lead to low DNA methylation levels (Frosst et al, 1995; van der Put et al, 1998).…”
Section: Epigeneticsmentioning
confidence: 99%
“…Hypermethylation in blood of nsCL/P was also observed. Li et al [ 21 ] reported hypermethylation of LINE-1 and IRF-6, together with LOC146880 from Howe et al [ 19 ] and CLASRP from Xu et al [ 20 ]. Li et al [ 21 ] collected data from the Chinese Defect Network to identify methylation in blood lymphocytes.…”
Section: Alterations In Dna Methylation Found In Blood Samples Of Pat...mentioning
confidence: 99%
“…Li et al [ 21 ] reported hypermethylation of LINE-1 and IRF-6, together with LOC146880 from Howe et al [ 19 ] and CLASRP from Xu et al [ 20 ]. Li et al [ 21 ] collected data from the Chinese Defect Network to identify methylation in blood lymphocytes. LINE-1 (long interspersed nucleotide element-1) has been widely accepted as a genomic biomarker and shows a strong correlation with levels of global DNA methylation in congenital anomalies [ 22 ].…”
Section: Alterations In Dna Methylation Found In Blood Samples Of Pat...mentioning
confidence: 99%
See 2 more Smart Citations